Impact of The Corporate Governance on Sustainability Report Disclosure with Environmental Performance as A Moderation Variable in Indonesia - Rumaningsih, Dewi Windary; Rusmanto, Toto (CV. Publikasi Indonesia, 2024)
This study aims to analyze the effect of corporate governance on sustainability report disclosure, with environmental performance acting as a moderating variable. The analysis focuses on the role of the board of directors, independent commissioners, audit committees, and financial performance in influencing the quality of sustainability reporting, particularly within the Indonesian context. Environmental performance is measured using the PROPER scale. The study utilizes data from the annual and sustainability reports of 20 companies in the basic materials and energy mining sectors listed on the Indonesia Stock Exchange from 2018 to 2022, amounting to 100 observations. The data is processed using SPSS 23. The results show that the presence of female directors significantly enhances the quality of sustainability disclosures, as they tend to prioritize social responsibility. Moreover, financial performance, as measured by Return on Assets (ROA), positively affects sustainability reporting, with companies in better financial health being more transparent in their disclosures. Environmental performance, when combined with strong independent oversight, further improves reporting quality, reflecting the positive influence of independent commissioners and sound financial governance. The study concludes that environmental performance, as measured by the PROPER scale, plays a significant role in improving sustainability disclosures in Indonesia. It recommends that the Indonesian government provide stronger support and clearer regulations to help companies improve their sustainability practices and contribute to the G20 agenda.